Characteristics of wind field at tunnel-bridge area in steep valley: Field measurement and LES study. (October 2022) - Yang, Weichao; Liu, Yikang; Deng, E.; Wang, Youwu; He, Xuhui; Lei, Mingfeng
Highlights: The wind shows a significant speed-up effect at the tunnel-bridge area. Von Kármán spectrum is applicable to describe the wind spectrum. The turbulence intensity linearly decreases in the large eddy simulation. Overhung anemometers are reasonable to be used at the tunnel-bridge area. Abstract: A high-speed train (HST) may be suddenly subjected to strong crosswinds when passing through a tunnel-bridge area in steep valley terrain. Investigating the natural wind characteristic at the tunnel-bridge area is helpful for the stability and safety of the HST. In this research, field measurement and large eddy simulation (LES) methods are applied to investigate the natural wind field characteristic at tunnel-bridge area in steep valley. The ultrasonic and three-cup anemometers are applied to investigate the mean and fluctuating wind characteristics, and the LES method is adopted to study the spatial distribution of corresponding wind field. The main conclusions are as follows: (1) A speed-up effect shows near the tunnel entrance and leads to a 37.5% increase in the wind speed; (2) A linear interpolation method is proposed to cope with the turbulence attenuation in LES modelling; (3) The turbulence intensity and ratios of turbulence intensities follow well with the log-normal distribution; (4) The von Kármán spectrum shows high applicability in describing the fluctuating wind field; (5) Coherence distances on u and v directions are approximately 8 times longer than the length of a train coach.